Journalists at risk : reporting America's wars - Sullivan, George, 1927- (Minneapolis, Minn. : Twenty-First Century Books, 2006)
Discusses the role of reporters during war time, including the risks they take and the censorship they face, and how their jobs have changed with each conflict since the Civil War.
From the front lines -- News by wire -- "Remember Pearl Harbor" -- Conflict in Korea -- The war in Vietnam -- Grenada and Operation Desert Storm --The War on Terrorism -- A fresh approach.
Includes bibliographical references (p. 119-123) and index.
Booklist, October 2005
6.4
5-8
Keywords: War correspondents; Journalism